Scientific research model in archeology: Theoretical design and methodological design for projects in Peru - Gonzalez Espino, David (2021)
Scientific research is a tool that allows researchers to develop works that have scientific quality criteria, to this is added a series of steps to build a research process. The objective of the work is to establish a model of scientific research in archeology, the specific objectives are; establish a working scheme with a theoretical criterion for archaeological research, and propose a working scheme with a methodological criterion for archaeological research.